Fetomaternal outcome in pregnant patients with Hepatitis-E infection - Tantray, Riyaz Ahmad; Quyoom, Darakhsha; Raina, Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Hepatitis E infection has been a major concern in pregnant women due to its fulminant nature in pregnancy compared to non-pregnant females and males. Hence the study was conducted for evaluating the maternal and perinatal outcome of pregnancy complicated by HEV infection. Methods: A prospective observational cohort study was conducted in department of obstetrics and gynaecology Deen Dayal Upadhyay Hospital, New Delhi, from January 2020 to June 2020. Pregnant women of gestational age≥28weeks with jaundice and positive for IgM Anti-HEV were part of study (sample size 36). Results: Hepatitis E virus infection adversely affects the maternal and fetal outcome with a maternal mortality of 11.1% noted in the study. Maternal complications observed were preterm labor (58.3%), PPROM (50.0%), PPH (47.2%), ICU admission (33.3%), fulminant hepatitis (11.1%), encephalopathy (11.1%). The common fetal complications noted were prematurity (47.2%), IUD (19.4%), NICU admission (47.2%). Conclusions: The study shows that pregnant women with jaundice and acute viral hepatitis due to hepatitis E virus infection had a high mortality rate especially during third trimester and postpartum period. Also, they have poor obstetric and foetal outcome.